2011
DOI: 10.1016/j.micres.2010.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of zinc oxide nanoparticles against Botrytis cinerea and Penicillium expansum

Abstract: Antifungal activities of zinc oxide nanoparticles (ZnO NPs) and their mode of action against two postharvest pathogenic fungi (Botrytis cinerea and Penicillium expansum) were investigated in this study. ZnO NPs with sizes of 70 ± 15 nm and concentrations of 0, 3, 6 and 12 mmol l(-1) were used. Traditional microbiological plating, scanning electron microscopy (SEM), and Raman spectroscopy were used to study antifungal activities of ZnO NPs and to characterize the changes in morphology and cellular compositions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
360
2
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 802 publications
(390 citation statements)
references
References 35 publications
24
360
2
4
Order By: Relevance
“…ZnO has already been shown to be effective against filamentous fungi in several studies (Sawai 2003; He et al 2011; Savi et al 2013) using conductimetry and growth diameter measurements. He et al investigated the antifungal effect of ZnO NPs with sizes of 70 ± 15 nm in concentrations ranging from 0 up to 12 mM against P. expansum (He et al 2011). Their results indicated that concentrations of ZnO NPs higher than 3 mM could significantly inhibit the radial growth of P. expansum onto Petri dishes, but no lower concentrations in the range between 0 and 3 mM were investigated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ZnO has already been shown to be effective against filamentous fungi in several studies (Sawai 2003; He et al 2011; Savi et al 2013) using conductimetry and growth diameter measurements. He et al investigated the antifungal effect of ZnO NPs with sizes of 70 ± 15 nm in concentrations ranging from 0 up to 12 mM against P. expansum (He et al 2011). Their results indicated that concentrations of ZnO NPs higher than 3 mM could significantly inhibit the radial growth of P. expansum onto Petri dishes, but no lower concentrations in the range between 0 and 3 mM were investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, cold storage atmosphere by itself does not prevent fruit rot since minimum temperatures for growth of P. expansum have been reported to be as low as −6°C, −3°C and −2°C (Brooks & Hansford 1923; Panasenko 1967; Pitt and Hocking 2009). In order to overcome these issues, it is important to explore novel antifungal agents which may replace current control strategies (He et al 2011). Recently, metal nanoparticles have received increasing attention due to strong antimicrobial properties and low toxicity towards mammalian cells and have been already applied in food preservation, burn dressings, safe cosmetics, medical devices, water treatment and other range of products (Moritz and Geszke-Moritz 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 The mechanisms of killing the fungi by ZnO NPs in different species is different, as it can alter the cellular function that result in deformation of fungal hyphae from one side and also it can disturb in development of conidia and conidiaphores and killing of hyphae. 25 One study claimed both nano and bulk ZnO showed comparable toxicity to yeast Saccharomyces cerevisiae (8-h EC50 121-134 mg ZnO/l and 24-h EC50 131-158 mg/l respectively), 26 whenever it was shown the bulk form of ZnO is more less effective to C. Albicans and other fungi in comparison to MgO, CaO and ZnO NPs could well inhibit the growth of fungi consisted of C. Albicans. 27,28 The synergism of antifungal and antioxidant effects of ZnO NPs that enhances antifungal effect of these NPs material is the other subject of discussion in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Among different types of nanoparticles, zinc oxide nanoparticles have extensive applications in cosmetics and sunscreen lotions because of their efficient UV-A and UV-B absorption properties without scattering visible light (Schilling et al, 2010). Zinc oxide nanoparticles possess excellent antimicrobial (Jin et al, 2009;Gerloff et al, 2012;), and anticancer properties (He et al, 2011) and also used in agriculture (Rasmussen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%